Efficacy of estradiol-dydrogesterone and auto-crosslinked hyaluronan gel in preventing intrauterine adhesions following missed miscarriage curettage: a retrospective observational study - Sheng, Huilin; Sui, Mengyun; Zhang, Lin; Shi, Jingfang; Xue, Long (Frontiers in Reproductive Health, 2025)
ObjectiveCurettage is a common treatment for missed abortion (MA). However, intrauterine adhesions (IUA) are a major postoperative problem that can lead to infertility and menstrual abnormalities. This study aimed to evaluate the effectiveness of estradiol-dydrogesterone (ED), auto-crosslinked hyaluronan (AH) gel, and their combination in preventing IUA following MA curettage.MethodsA retrospective cohort study was conducted between June 2022 and December 2023. A total of 284 women following MA curettage were included, with 265 completing follow-up assessments. Participants were divided into four groups: (1) ED group (oral estradiol-dydrogesterone therapy), (2) AH group (intrauterine AH gel application), (3) ED + AH group (combination therapy), and (4) control group (no intervention). IUA diagnosis was confirmed via hysteroscopy.ResultsThe incidence of IUA was significantly lower in the intervention groups compared to the control group (p = 0.001). The IUA rates were 7.94% in the ED group, 6.15% in the AH group, 5.71% in the ED + AH group, and 23.88% in the control group. Logistic regression analysis identified a significant reduction in IUA risk for patients receiving ED (OR = 0.17, p = 0.005), AH (OR = 0.13, p = 0.002), and ED + AH (OR = 0.15, p = 0.005) compared to the control group. Additionally, a history of three or more miscarriages was associated with a higher risk of IUA (OR = 4.34, p = 0.027).ConclusionThis study demonstrates that prophylactic treatment with ED and/or AH significantly reduces the incidence of IUA following curettage for MA. These findings underscore the importance of individualized endometrial repair and adhesion prevention strategies in preserving female reproductive health.